PENGARUH PENERAPAN MODEL DISCOVERY LEARNING TERHADAP HASIL BELAJAR SUBTEMA KEBERSAMAAN DALAM KEBERAGAMAN - Asofa Tanhara; Santa; Sri Rahayu Dwiastuti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The approach taken is a quasi-experimental design of two groups at Situ Gede 2 State Elementary School. These subjects are students of class IV A and IV B of Situ Gede 2 State Elementary School, Bogor City, consisting of 64 students. This research was conducted in the odd semester of the 2021 academic year. /2022. The results of the study show that there is an effect of "The Influence of Application of the Discovery Learning Model on Learning Outcomes of Togetherness in Diversity". This can be seen from the NGain value in the experimental class group of 63, while the control class group got an N-Gain value of 45. The results of hypothesis testing are that Ho is rejected and Ha is accepted because tcount (2.8708) > ttable (2.0261) . With this it can be concluded that the research has a significant positive effect between the Effects of Application of the Discovery Learning Model on Learning Outcomes of the Sub-theme of Togetherness in Diversity. The results of this study are expected to provide new knowledge regarding the application of innovative learning models and can improve learning outcomes.